Contributions to the Neuropsycholinguistic Analysis of the Williams Syndrome [Contribuciones al Análisis Neuropsicolingüístico del Síndrome de Williams] - Aguilar-Valera, José Alonso (2019)
ABSTRACT Williams’s syndrome is an unusual abnormality of neurodevelopment with a characteristic behavioral phenotype. The article shows a theoretical review of the clinical and language characteristics of this syndrome features, from a careful bibliographical synthesis. These will be described under a neuropsycolinguistic approach, with emphasis on semantic and pragmatic components of language and lexical-semantic information processing, being the main axes analyzed the deficit in verbal behavior of Williams’s syndrome. Also recognize the neuro-linguistic contributions of Luria. It is showed criteria for the understanding of the organizational principles of the language, associated with changes in the language of Williams’s syndrome. The article provides, from a child neuropsychology perspective, a greater understanding of abnormal neuropsycolinguistic features of Williams’s syndrome and conceptual strengthen for a future intervention.